2015
DOI: 10.1021/ic502791y
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis as a Platform for the Discovery of New Ruthenium Complexes for Efficient Release of Photocaged Ligands with Visible Light

Abstract: Ruthenium-based photocaging groups have important applications as biological tools and show great potential as therapeutics. A method was developed to rapidly synthesize, screen and identify ruthenium-based caging groups that release nitriles upon irradiation with visible light. A diverse library of tetra- and pentadentate ligands was synthesized on polystyrene resin. Ruthenium complexes of the general formula [Ru(L)(MeCN)n]m+ (n = 1–3, m = 1–2) were generated from these ligands on solid phase, then cleaved fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 104 publications
(193 reference statements)
2
27
0
Order By: Relevance
“…A comparison between the bond angles of 1 and 2 reveals that the only difference is that in 2 the N6 CH 3 CN cis to the basic amine nitrogen is tilted slightly toward the N2 arm, as evidenced by the slightly smaller N6–Ru1–N2 angle of 86.99(3)° in 2 as compared to 93.00(7)° in 1 . Again, the Ru–N bond lengths in 2 are comparable to 1 , as well as to those of the previously reported [Ru(TQA)(CH 3 CN) 2 ] 2+ 58 . In addition, the Ru–N(CH 3 CN) bond lengths in 2 also compare well with those reported for cis -[Ru(bpy) 2 (CH 3 CN) 2 ] 2+ 88.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A comparison between the bond angles of 1 and 2 reveals that the only difference is that in 2 the N6 CH 3 CN cis to the basic amine nitrogen is tilted slightly toward the N2 arm, as evidenced by the slightly smaller N6–Ru1–N2 angle of 86.99(3)° in 2 as compared to 93.00(7)° in 1 . Again, the Ru–N bond lengths in 2 are comparable to 1 , as well as to those of the previously reported [Ru(TQA)(CH 3 CN) 2 ] 2+ 58 . In addition, the Ru–N(CH 3 CN) bond lengths in 2 also compare well with those reported for cis -[Ru(bpy) 2 (CH 3 CN) 2 ] 2+ 88.…”
Section: Resultssupporting
confidence: 87%
“…Like [Ru(TPA)(CH 3 CN) 2 ] 2+ and [Ru(TPA)(py) 2 ] 2+ , irradiation of [Ru(TQA)(CH 3 CN) 2 ] 2+ only results in ligand exchange of the CH 3 CN positioned cis to the basic amine nitrogen of the TQA ligand. 58 Calculations provided an explanation for the increase and selectivity of ligand exchange, showing the presence of favorable orbital overlap in the excited state between the coplanar quinoline arms of the TQA ligand and the photolabile CH 3 CN ligand that is not present in the TPA complex. 59 …”
Section: Introductionmentioning
confidence: 98%
“…44 In an effort to tune the photochemistry of the Ru(TPA) caging group, ligands derived from TPA were designed and analyzed for photochemical reactivity of Ru(II) nitrile complexes. 45 Results revealed that absorptivity is shifted readily into the visible range upon tuning the ligand structure. However, a wide range of reactivities with light was observed for complexes derived from very similar ligands, even though several complexes absorbed light in the visible range.…”
Section: Introductionmentioning
confidence: 99%
“…48 Briefly, Ru(II)-caged MeCN complexes were synthesized using a library of TPA derivatives obtained on polystyrene resin, which were then metalated using fac -[Ru(DMSO) 3 (O 2 CCCF 3 ) 2 (H 2 O)], converted into caged nitriles upon treatment with MeCN/H 2 O, and cleaved from the resin for photochemical analysis (Figure 4). The data show a wide range of spectral tuning and reactivity with visible light for these complexes.…”
Section: The Development Of Ru(tpa) For Photocagingmentioning
confidence: 99%
“…1,4346 The three-dimensional geometry and tunable photophysical properties also make Ru(II) polypyridyl complexes attractive photocaging agents. 27,4648 …”
Section: Introductionmentioning
confidence: 99%